Asset pricing with distorted beliefs are equity returns too good to be true? - Cecchetti, Stephen G. 1956-; Lam, Pok-sang; Mark, Nelson C. (1998)
We study a Lucas asset pricing model that is standard in all respects representative agent's subjective beliefs about endowment growth are distorted. Using constant-relative-risk-aversion (CRRA) utility a CRRA coefficient below ten that exhibit, on average, excessive pessimism over expansions and excessive optimism over contractions, our model is able to match the first and second moments of the equity premium and risk-free rate, as well as the persistence and predictability of excess returns found in the data.
Keywords: Ökonometrisches Modell; Assets (Accounting) -- Prices -- United States -- Forecasting -- Econometric models; Rate of return -- United States -- Forecasting -- Econometric models; Rational expectations (Economic theory) -- United States -- Econometric models; USA